KINETICS AND MECHANISM OF LIGAND-PROMOTED DECOMPOSITION OF THE KEGGIN AL13 POLYMER - Amirbahman A.; Gfeller M.; Furrer G. (My University, 2000)
The effect of five low molecular weight organic acids (oxalate, malonate, salicylate, phthalate and benzoate) on the decomposition kinetics of the Al13 polymer was studied in acidic aqueous solutions using a flow-through reactor that was operated under steady-state conditions. The results showed that those ligands that can form bidentate complexes with ''surface'' octahedral Al(III) centers are able to decompose Al13. Decomposition rates increased with increasing proton and ligand concentrations in the pH range studied (2.0 < pH < 4.8).Modeling of the decomposition process indicated the existence of two independent and parallel proton- and ligand-promoted pathways. The former pathway has been studied previously. We propose that the Al13-ligand complex (Al13L5+) is the precursor to the ligand-promoted decomposition. The rate of decomposition can be described as first-order with respect to the RL=-kLa[Al13L5+] where the apparent ligand-promoted decomposition rate coefficient (kLa) generally has a first- and a second-order dependence on the proton concentration as kLa=kL1[H+]+kL2[H+]2 For oxalate at the pH range studied, second-order dependence on [H+] was negligible, possibly because of the ligand's strong acidic character. At pH > 4, equimolar concentrations of the bidentate ligands enhanced the kinetics of Al13 decomposition by factors of up to 20 in comparison to proton-promoted decomposition in ligand-free solutions. The most distinct impact was observed for oxalate and phthalate followed by malonate. The monodentate ligand benzoate had no influence on the half-life of Al13. In contrast to the effects of ligands on the dissolution kinetics of solid δ-Al2O3, where salicylate is a powerful promoter, the kinetics of Al13 decomposition is enhanced only very little by salicylate. This difference in reactivity of solid aluminum oxide and the dissolved Al13 polymer towards the investigated bidentate ligands can be attributed to the different coordination geometry of the surface Al(III) centers in the two aluminum compounds. Based upon the order of reactivity of the ligands used in this study, we propose that the rate-determining step in the ligand-promoted decomposition of Al13 is formation of a ''surface'' bidentate complex.